Informational Loss in Bundled Bargaining - Ying Chen; Hülya Eraslan (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We analyze a legislative bargaining game over an ideological and a distributive issue. Legislators are privately informed about their ideological positions. Communication takes place before a proposal is offered and majority rule voting determines the outcome. We compare the outcome of the "bundled bargaining" game in which the legislators negotiate over both issues together to that of the "separate bargaining" game in which the legislators negotiate over the issues one at a time. Although bundled bargaining allows the proposer to use transfers as an instrument for compromise on the ideological issue, we identify two disadvantages of bundled bargaining under asymmetric information: (i) risk of losing the surplus (failure to reach agreement on ideology results in the dissipation of the surplus under bundled bargaining, but not under separate bargaining); (ii) informational loss (the legislators may convey less information in the bundled bargaining game). Even when there is no risk of losing the surplus, the informational loss from bundling can be sufficiently large that it makes the proposer worse off.
Keywords: 330; Gesetzgebung; Politische Entscheidung; Ideologie; Informationsverbreitung; Verhandlungstheorie; Spieltheorie